2003
DOI: 10.1034/j.1600-0463.2003.1110104.x
|View full text |Cite
|
Sign up to set email alerts
|

Early manifestations of testicular dysgenesis in children: pathological phenotypes, karyotype correlations and precursor stages of tumour development

Abstract: Testicular dysgenesis derives from abnormal gonadal development caused by chromosome aberrations/mosaicisms or mutations/deletions in SRY or other genes responsible for testicular differentiation. Dysgenetic male pseudohaermaphroditism has bilateral dysgenetic testes characterized by a cortical network of anastomosing seminiferous cords that penetrate a thin albuginea. In asymmetric gonadal differentiation (or Mixed Gonadal Dysgenesis) a dysgenetic testis associates with a streak gonad with primitive sex cords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 34 publications
(30 reference statements)
2
56
0
4
Order By: Relevance
“…21 The well-known syndromes associated with a risk for tumor development are: mixed gonadal dysgenesis, some patients with Turner phenotype and in several cases of 46,XY male pseudohermaphroditism. [2][3][4][5][6][7] There is also a reported case of this type of tumor in a 46,XX/46,XY true hermaphrodite. 6 The tumor development in these patients had been associated with the presence of normal or abnormal Y-chromosomes, molecular evidence for Y-derived sequences and intrabdominal location of the abnormal gonads.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…21 The well-known syndromes associated with a risk for tumor development are: mixed gonadal dysgenesis, some patients with Turner phenotype and in several cases of 46,XY male pseudohermaphroditism. [2][3][4][5][6][7] There is also a reported case of this type of tumor in a 46,XX/46,XY true hermaphrodite. 6 The tumor development in these patients had been associated with the presence of normal or abnormal Y-chromosomes, molecular evidence for Y-derived sequences and intrabdominal location of the abnormal gonads.…”
Section: Discussionmentioning
confidence: 93%
“…6 The tumor development in these patients had been associated with the presence of normal or abnormal Y-chromosomes, molecular evidence for Y-derived sequences and intrabdominal location of the abnormal gonads. 3,4,7,8,18 The age at diagnosis is variable ranging from birth to the fourth decade; around 94% of cases Distribution of Y-chromosome-bearing cells R Peña-Alonso et al reported in the literature was diagnosed during the second or third decades of life. 22 Data in the literature revealed 10 cases where the tumor developed during childhood, five of them had a 45,X/ 46,XY mixed gonadal dysgenesis and the diagnosis was performed only in one case at 9 months old while the rest were diagnosed around 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40][41][42] 43 have shown a strong correlation between the presence of the Y chromosome and the severity of the gonadal dysgenesis. Gonadoblastoma acts as an 'in situ' precursor in these patients.…”
Section: Pathogenesismentioning
confidence: 99%